BLOODLANDS AND BURNED PEOPLE: REMARKS ON THE EMERGENCE AND FUNCTIONS OF THE ARCADIAN IMAGE OF BOHEMIA IN POLISH LITERATURE AND ITS DESTRUCTION IN SAPKOWSKI’S HUSSITE TRI - Hanczakowski, Michał (Prace Polonistyczne, 2019)
The main aim of the article is to examine the representation of Bohemia in contemporary Polish literature. The first part of the text focuses on the early stage of its mythologization, in which Czech lands became a point of reference for Polish writers in the times of the emergence of the term “Central Europe” in Polish discourse. The author presents the concepts taken from Milan Kundera’s and Josef Kroutvor’s essays as critical in shaping the perception of Bohemia as a land where, unlike in Polish historical discourse, history does not serve a source of trauma. This Arcadian vision of Czech history is strongly present in Mariusz Szczygieł’s texts, which can be seen as playing the key role in the mythologization of Czech lands in Polish imagination. The second part of the text concentrates on the historical narrative in Andrzej Sapkowski’s Hussite Trilogy and its references to the history of Central Europe. In the trilogy Bohemia and Silesia are consistently presented as bloodlands and a source of trauma, not only in contemporary times but in medieval history as well.